RISET MIKRO KINERJA PEGAWAI DPMG KABUPATEN PIDIE JAYA: DARI KAJIAN KEPEMIMPINAN, PEMBERDAYAAN PEGAWAI DAN MOTIVASI KERJA - Amri, Ulil; Azhari; Musrizal (IndOmera, 2024)
This research was conducted on a micro scale to study the performance of employees of the Community and Gampong Empowerment Service (DPMG) in Pidie Jaya Regency. The things studied are based on leadership factors, employee empowerment and work motivation. The form of survey research uses a questionnaire with the subject respondents being 42 employees in the office. Meanwhile, hypothesis testing and research analysis use the path analysis model. The research results found: (a) The contribution of leadership factors, employee empowerment and work motivation in efforts to maintain employee performance is quite large, namely 32.92%. (B). Causality analysis proves that there is a significant relationship between leadership and employee empowerment (R=0.331), between employee empowerment and work motivation (R= 0.419) and there is a causal relationship between motivation and leadership (R= 0.441). (c) Leadership aspects have a direct and indirect influence on employee performance by 45.27%. The employee empowerment aspect has an influence on employee performance by 39.59% and the contribution of work motivation to employee performance is 32.92%.